?LOCAL DEVELOPMENT OF PEG ASSISTED DOUBLE ANTIBODY T4-R-\DIOIMMUNOASSAY (Biological Sciences - PJSIR, 2001)
In order to replace expensive ready-made commercial radioimmunoassay (RIA) kits with high quality local techniques a local Throxine (F) RIA was developed and evaluated. Four basic components of immunoassay system, antibody, radiotracer, standards and precipitating solutions were locally prepared. Twelve rabbits were immunized to produce primary antibodies against T4using T4 conjugated with human serum albumin (HSA) and emulsified with Freund's adjuvant as immunogen. Results showed that 4 out of 12 rabbits responded well to the immunogen and a maximum titre of 1:9700 was achieved with a working dilution from 1:1000 to 1:10000. Radioidination of Triiodothyronine (T3) to produce radiotracer, 12.\I-T4(and 125I-T3) by chloramine-T method showed that 31% of radioactivity was bound to T3 and 50% to T4with specific activities of(11.1-14.8 MBq/JJg) and (1.85-2.22 MBq/JJg) respectively. Second antibody against T4 was raised in two sheep. Results of optimization of second antibody showed a working dilution 1:60 for T4- RIA. Precipitating solution to separate antigen antibody complex was prepared by mixing sheep anti-rabbit serum (SARS) with phosphate buffer containing 4% polyethlene glycol (PEG) at working dilution. PEG assisted double antibody T4-RIA showed more than 7% error in the concentrations below 10 nmol/l with high precision at higher concentrations. The results of quality control samples showed that the values were within expected limits. The values correlated well with the commercial techniques (ICN; Corr. Coeff=0.99) and the values of patient samples determined in commercial as well as in house techniques did not differ significantly (p